2021
DOI: 10.1136/bmjresp-2020-000844
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high flow nasal oxygen for children with bronchiolitis: systematic review and meta-analysis

Abstract: BackgroundTo assess the published evidence to establish the efficacy and safety of high flow oxygen cannula (HFNC) as respiratory support for children up to 24 months of age with bronchiolitis within acute hospital settings.MethodsWe searched eight databases up to March 2021. Studies including children up to 24 months of age with a diagnosis of bronchiolitis recruited to an randomised controlled trial were considered in the full meta-analysis. At least one arm of the study must include HFNC as respiratory supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
1
24
0
3
Order By: Relevance
“…Thus, the low incidence of VDD in studies showing no correlation between the severity of disease and vitamin D [1,2] is a significant limitation to consider when interpreting their results. Conversely, studies with larger sizes and higher rates of VDD [3,4] had conclusions similar to ours [1]. We also agree with the comment about the relevance of age and prematurity on the severity of acute bronchiolitis.…”
Section: Authors' Replysupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the low incidence of VDD in studies showing no correlation between the severity of disease and vitamin D [1,2] is a significant limitation to consider when interpreting their results. Conversely, studies with larger sizes and higher rates of VDD [3,4] had conclusions similar to ours [1]. We also agree with the comment about the relevance of age and prematurity on the severity of acute bronchiolitis.…”
Section: Authors' Replysupporting
confidence: 89%
“…Another issue we want to draw attention to is that the NIV was used with a high frequency of 25% in this study [1], but the details about the NIV methods are lacking. A meta-analysis of 15 studies [4] showed that high-flow nasal oxygen therapy is beneficial and safe, with similar failure rates with continuous positive airway pressure. Secondly, bi-level positive pressure ventilation has been reported to be associated with longer PICU stay and prolonged ventilation needs [5].…”
Section: C C C C O O O O O R R R R R R R R R R E E E E E S S S S S P ...mentioning
confidence: 99%
“…Appropriate resource allocation and preparation is needed now, with changes in departments needed akin to how we prepared for the surges in COVID-19 infections. This should include redeployment of clinical staff to manage the increased numbers of patients, up-to-date training on bronchiolitis guidelines, including use of highflow oxygen on acute paediatric wards, 6 and public health advice to reinforce the importance of NPI practices such as handwashing to reduce the spread of RSV.…”
Section: Lettermentioning
confidence: 99%
“…Recent data suggest beneficial effects of high-flow nasal cannula (HFNC), which combines the administration of oxygen with the application of positive airway pressure, all of which decreases work of breathing and improves gas exchange. HFNC therapy should be performed in highdependency units or ICU (90).…”
Section: Treatment Of Severe Casesmentioning
confidence: 99%